A APLIKASI KOMPOS LIMBAH PERTANIAN PADA BUDIDAYA TOMAT (Lycopersicum esculentum MILL.): APLIKASI KOMPOS LIMBAH PERTANIAN PADA BUDIDAYA TOMAT (Lycopersicum esculentum MILL.) - Gunawan Budiyanto; Maulela Ajar Ridzany; Hariyono Hariyono (Innofarm:Jurnal Inovasi Pertanian, 2021)
From January to July 2016, greenhouse research named "The Effect of Diverse Agricultural Waste on the Growth and Yield of Tomato (Lycopersicum esculentum Mill.)" was done to assess the potential for various agricultural waste to be used as organic fertilizer (compost) in tomato growing. The experiment was conducted with a single factor and a Completely Randomized Design (CRD). The treatments were as follows: 200 kilograms Urea per hectare, 300 kilograms SP-36 per hectare, and 200 kilograms KCl per hectare (P0); 20 tons cow manure per hectare + 200 kilograms Urea per hectare, 300 kilograms SP-36 per hectare, and 200 kilograms KCl per hectare (P1); 6.504 tons rice-straw compost per hectare + 200 kilograms Urea per hectare, 300 kilograms SP-36 per hectare (P4). Each treatment was administered a total of twelve times. The results indicated that (1) compost made from various agricultural wastes, such as rice straw, corn litter, and cassava peel, had a significant effect on the growth and yield of tomato plants; and (2) a dose of 6,504 tons/ha Rice Straw compost + 200 kg Urea per hectare, 300 kg SP-36 per hectare, and 200 kg KCl per hectare can increase the growth and yield of tomato plants